INFORMATION SYSTEM FOR INTERNSHIP ADMISSIONS WEB-BASED (CASE STUDY: CIREBON POST OFFICE) - Wiwiek Nurkomala Dewi; Novan Novan; Suwandi Suwandi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The registration information system is an information system flow where students who will register at the post office use an application/web mechanism. For this reason, the post office seeks to maximize efforts in providing an easy, effective and efficient way for student applicants at the Cirebon Post Office. In this case the author designed a registration program using the programming languages ​​php, css, mysql, javascript and then compiled a flowmap and uml. In data collection and design, then the data collection process such as interviews and analysis at the Post Office. This will provide a solution for designing a registration application design with an easy and attractive user interface so that in this design the editing software used is figma and it contains student internship registration information such as dashboards, registrant files and edit profiles. The internship registration information system at the post office is a means to assist agencies and students in the registration process to make it easier to manage application system data effectively and efficiently. so that the author can provide suggestions for future development so that the application can be accessed online, and can contain news or information about the Cirebon post office